Consistency Cone Penetrometry for Food Products - Kakimov, Aitbek; Yessimbekov, Zhanibek; Bepeyeva, Aigerim; Kabulov, Bolat; Kakimova, Zhainagul (Pakistan Journal of Nutrition, 2015)
This study describes the operational principle of cone penetrometers and method of determining the yield stress using cone penetrometers. The standard GOST R 50814-95 “Meat products. Methods of penetration determination by means of the cone and the needle indentor”, developed by the Russian Federation in 1995, applies to viscous-plastic (meat and sausage forcemeat, pate) and elastic (ready meat and sausage) meat products and specifies the methods of consistency determination by cone or needle penetration. The test method for penetration of viscous-plastic materials using different penetrometers and the main equations for yield stress determination are presented.